Rutin inhibits quorum sensing, biofilm formation and virulence genes in avian pathogenic Escherichia coli. (June 2018) - Peng, Lu-Yuan; Yuan, Meng; Cui, Zhen-Qiang; Wu, Zong-Mei; Yu, Zhen-Jiang; Song, Ke; Tang, Bo; Fu, Ben-Dong
Abstract: The study aimed to investigate whether rutin affects the quorum sensing (QS) of avian pathogenic Escherichia coli (APEC). In this study, APEC-O78 was selected as the test strain. We mainly examined the effects of rutin on the AI-2 secretion by bioluminescence assay, biofilm formation through a crystal violet staining method, and expression of virulence genes of APEC by qRT-PCR. We found that rutin can significantly interfering with QS through reducing the secretion of AI-2, inhibited the biofilm formation, and reduced the expression of virulence genes of APEC. Moreover, rutin markedly decreased adhesion and damage of APEC to chicken type II pneumocytes. These results suggested rutin reduces cell damage of APEC-infected chicken type II pneumocytes through interfering with QS via decreasing AI-2 production, biofilm formation, and the expression of virulence genes. This paper may provide a new evidence for colibacillosis prevention in chicken. Highlights: Rutin significantly reduced the secretion of AI-2 to interfere with quorum sensing. Rutin markedly inhibited the biofilm formation of APEC. Rutin remarkably reduced the expression of virulence genes of APEC. Rutin markedly decreased adhesion and damage of APEC to chicken type II pneumocytes.